Stereoselective Metabolism of Bupropion by Cytochrome P4502B6 (CYP2B6) and Human Liver Microsomes - Coles, Rebecka (2008)
PURPOSE: Hydroxylation of the antidepressant and smoking deterrent drug bupropion is a clinically important bioactivation and elimination pathway. Bupropion hydroxylation is catalyzed selectively by cytochrome P4502B6 (CYP2B6). CYP2B6-catalyzed bupropion hydroxylation has been used as an in vitro and in vivo phenotypic probe for CYP2B6 activity and CYP2B6 drug interactions. Bupropion is chiral, used clinically as a racemate, and disposition is stereoselective. Nevertheless, it is unknown whether CYP2B6-catalyzed bupropion hydroxylation is stereoselective. METHODS: Hydroxylation of racemic bupropion by recombinant CYP2B6 and human liver microsomes was evaluated using a stereoselective assay. RESULTS: At therapeutic concentrations, hydroxylation of (S)-bupropion was 3-fold and 1.5-greater than (R)-bupropion, respectively, by recombinant CYP2B6 and human liver microsomes. In vitro intrinsic clearances were likewise different for bupropion enantiomers. CONCLUSIONS: Stereoselective bupropion hydroxylation may have implications for the therapeutic efficacy of bupropion as an antidepressant or smoking cessation therapy, and for the use of bupropion as an in vivo phenotypic probe for CYP2B6 activity.